2020
DOI: 10.1017/dmp.2020.383
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Propagation of COVID-19 in the UK

Abstract: COVID-19 was first identified in December 2019 in Wuhan, China. From the beginning, this disease has been the subject of various scientific studies. Due to the large amount of data related to the spread of COVID-19 and the high speed of changes, particularly in modeling and forecasting works, it is required to update the predictions and assess the goodness of performance or the accuracy of the models. In this regard, we aim at evaluating the performance of the model introduced by Jamshidi et al [1] to describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…1 Generally, COVID-19 is more severe in people aged >60 years or those with underlying diseases. 2,3 Research on COVID-19 has been conducted from various perspectives, such as infection cases, 4,5 clinical characteristics, [6][7][8] and preventive measures. 9 In addition, several studies have confirmed that COVID-19 is more severe in older people and those with underlying diseases, such as lung or heart disease, diabetes, and immunological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 Generally, COVID-19 is more severe in people aged >60 years or those with underlying diseases. 2,3 Research on COVID-19 has been conducted from various perspectives, such as infection cases, 4,5 clinical characteristics, [6][7][8] and preventive measures. 9 In addition, several studies have confirmed that COVID-19 is more severe in older people and those with underlying diseases, such as lung or heart disease, diabetes, and immunological diseases.…”
Section: Introductionmentioning
confidence: 99%